The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/08957959.2012.745860
|View full text |Cite
|
Sign up to set email alerts
|

Is high pressure treatment able to modify the allergenicity of the largemouth bass allergens?

Abstract: The aim of this paper is to study the influence of high pressure treatment on the structural changes and allergenicity of largemouth bass. We treated the allergens at 100, 200, 300 and 400 MPa for 15 min and at 300 MPa for 5, 10, 15, 20 and 30 min at 20 • C. The treated samples from largemouth bass were tested for their IgE-binding properties by combining Sodium dodecyl sulfate-Polyacrylamide gel electrophoresis (SDS-PAGE) with western blotting (WB) and enzyme-linked immunosorbent assay (ELISA). Circular dichr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Bi granules (purity 99.999%, Alfa Aesar) were compressed into cylinders (ø6mm×6mm ) and subjected to HP-HT treatments in a six-anvil high pressure apparatus [23]. The HP-HT conditions are presented in [24](Table SI).…”
mentioning
confidence: 99%
“…Bi granules (purity 99.999%, Alfa Aesar) were compressed into cylinders (ø6mm×6mm ) and subjected to HP-HT treatments in a six-anvil high pressure apparatus [23]. The HP-HT conditions are presented in [24](Table SI).…”
mentioning
confidence: 99%
“…For example, the apple allergens, Mal d 1 and Mal d 1 responded to HHP by reducing their immunoreactivities in one study [20] and yet no effects were reported in another study [21]. Also, HHP resistant nature of fish allergens (Gad m 1 and largemouth bass) were reported with limited influence on their protein structures and immunoreactivities [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The HP technique has been used for the reduction of microbial contaminants and has demonstrated advantages of retaining sensory and nutritional values in comparison with thermal techniques. HP treatment causes denaturation through disruption of hydrogen bonds when applied above 150 MPa, changes in intramolecular forces above 200 MPa and induction of refolding of low‐molecular‐weight proteins at pressures above 400 MPa . The HP technique was applied for decreasing the allergenicities or antigenicities of soybeans, rice, apple juice and peanuts …”
Section: Introductionmentioning
confidence: 99%
“…HP treatment causes denaturation through disruption of hydrogen bonds when applied above 150 MPa, changes in intramolecular forces above 200 MPa and induction of refolding of low-molecular-weight proteins at pressures above 400 MPa. 20 The HP technique was applied for decreasing the allergenicities or antigenicities of soybeans, 10,21 rice, 16 apple juice 22 and peanuts. 23 In this research, we explored multiplexed methods for reducing allergenicity.…”
Section: Introductionmentioning
confidence: 99%